Assessing physical activity and sedentary lifestyle behaviours for children and adolescents living in a district of Poland. What are the key determinants for improving health? - Paulina Wojtyła-Buciora; Barbara Stawińska-Witoszyńska; Krzysztof Wojtyła; Aneta Klimberg; Cezary Wojtyła; Andrzej Wojtyła; Danuta Samolczyk-Wanyura; Jerzy T. Marcinkowski (Annals of Agricultural and Environmental Medicine, 2014)
[b]Introduction.[/b] Adequate levels of physical activity throughout an individual’s life ensure an optimal state of health. Only 30% of adolescents and 10% of adults perform sufficient physical activity to facilitate proper physical, psychological/mental and emotional development. [b]Objective[/b]. Determining physical activity behaviour in children and adolescents through surveying the opinions of school pupils and parents, in order to lend support for optimised educational programmes designed to promote healthy lifestyle behaviour, as well as establishing consistent answers. [b]Materials and Methods[/b]. A randomised survey was conducted on two groups of n=1100 pupil subjects, each attending elementary or secondary school, with the former in Classes 5 and 6, whereas the latter were aged between 16–19 years old; in both instances parents were also included in the survey. All subjects came from the Kalisz District in western-central Poland, and were divided into those living in the city of Kalisz and those in the surrounding rural areas. [b]Results[/b]. It was found that 87%, 96% and 89% of elementary, middle and secondary school pupils, respectively, participated in Physical Education (PE) lessons. The numbers of pupils who daily, or almost daily, spent time on a computer, were 52%, 60% and 70%, respectively, for elementary, middle and secondary schools, and likewise 70%, 62% and 48% for watching TV. [b]Conclusions[/b]. It is vital that education programmes with a focus on a healthy lifestyle are introduced and targeted at teenagers in order to promote physical activity during the crucial time of the body’s development. The period of maturing into adulthood is particularly crucial for acquiring the right knowledge, convictions, skills and attitudes that help shape a pro-healthy lifestyle in later years.